Economic Evaluation of a Patient-Directed Music Intervention for ICU Patients Receiving Mechanical Ventilatory Support*. Issue 9 (September 2018) - Chlan, Linda L.; Heiderscheit, Annette; Skaar, Debra J.; Neidecker, Marjorie V.
Abstract : Objectives: Music intervention has been shown to reduce anxiety and sedative exposure among mechanically ventilated patients. Whether music intervention reduces ICU costs is not known. The aim of this study was to examine ICU costs for patients receiving a patient-directed music intervention compared with patients who received usual ICU care. Design: A cost-effectiveness analysis from the hospital perspective was conducted to determine if patient-directed music intervention was cost-effective in improving patient-reported anxiety. Cost savings were also evaluated. One-way and probabilistic sensitivity analyses determined the influence of input variation on the cost-effectiveness. Setting: Midwestern ICUs. Patients: Adult ICU patients from a parent clinical trial receiving mechanical ventilatory support. Interventions: Patients receiving the experimental patient-directed music intervention received a MP3 player, noise-canceling headphones, and music tailored to individual preferences by a music therapist. Measurements and Main Results: The base case cost-effectiveness analysis estimated patient-directed music intervention reduced anxiety by 19 points on the Visual Analogue Scale-Anxiety with a reduction in cost of $2, 322/patient compared with usual ICU care, resulting in patient-directed music dominance. The probabilistic cost-effectiveness analysis found that average patient-directed music intervention costs were $2, 155 less than usual ICU care and projected that cost saving is achieved in 70% of 1, 000 iterations. Based on break-even analyses, cost saving is achieved if the per-patient cost of patient-directed music intervention remains below $2, 651, a value eight times the base case of $329. Conclusions: Patient-directed music intervention is cost-effective for reducing anxiety in mechanically ventilated ICU patients. Abstract : Supplemental Digital Content is available in the text.